2014
DOI: 10.1051/0004-6361/201424716
|View full text |Cite
|
Sign up to set email alerts
|

Wind bubbles within H ii regions around slowly moving stars

Abstract: Interstellar bubbles around O stars are driven by a combination of the star's wind and ionizing radiation output. The wind contribution is uncertain because the boundary between the wind and interstellar medium is difficult to observe. Mid-infrared observations (e.g., of the H ii region RCW 120) show arcs of dust emission around O stars, contained well within the H ii region bubble. These arcs could indicate the edge of an asymmetric stellar wind bubble, distorted by density gradients and/or stellar motion. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 69 publications
(149 reference statements)
11
108
2
1
Order By: Relevance
“…X-ray observations with XMM-Newton of AE Aurigae (HIP 24575) revealed for the first time significant emission, but its nature (very hot thermal or non-thermal) could not be firmly determined (López-Santiago et al 2012). In the case of ζ Ophiuchi, Toalá et al (2016) detected diffuse emission in the vicinity of this candidate, which they attribute to a plasma with a temperature of 2 · 10 6 K, in agreement with predictions of high plasma temperatures caused by instabilities mixing material between the shocked wind and the photo-ionized gas at the wake of the shock (Mackey et al 2015). Recently, (Toalá et al 2017) showed that the X-ray emission close to AE Aurigae is point-like and unrelated to the bow shock.…”
Section: Introductionsupporting
confidence: 79%
“…X-ray observations with XMM-Newton of AE Aurigae (HIP 24575) revealed for the first time significant emission, but its nature (very hot thermal or non-thermal) could not be firmly determined (López-Santiago et al 2012). In the case of ζ Ophiuchi, Toalá et al (2016) detected diffuse emission in the vicinity of this candidate, which they attribute to a plasma with a temperature of 2 · 10 6 K, in agreement with predictions of high plasma temperatures caused by instabilities mixing material between the shocked wind and the photo-ionized gas at the wake of the shock (Mackey et al 2015). Recently, (Toalá et al 2017) showed that the X-ray emission close to AE Aurigae is point-like and unrelated to the bow shock.…”
Section: Introductionsupporting
confidence: 79%
“…The H  region and wind bubble can become distorted if the star is moving (Weaver et al 1977;Raga et al 1997;Meyer et al 2014), and if the star moves supersonically through the H  region then the wind bubble drives a bow shock in the direction of motion (Baranov et al 1971;Weaver et al 1977;Arthur & Hoare 2006;Zhu et al 2015). In Mackey et al (2015, hereafter Paper I), we showed that even slowly moving stars (space velocity, v = 4 km s −1 ) produce very asymmetric wind bubbles in dense regions.…”
Section: Introductionmentioning
confidence: 65%
“…Also, the shape of astrospheres of hot (runaway) stars might be affected by photoevaporation flows from nearby regions of enhanced density (cloudlets) caused by ultraviolet emission of these stars (e.g. Mackey et al 2015;Gvaramadze et al 2017). Fig.…”
Section: Observational Datamentioning
confidence: 99%